Direct Shear Behavior of a Mixture of Sand and Tire Chips Using X-ray Computed Tomography and Discrete Element Method - Chevalier, Bastien; Tsutsumi, Yohei; Otani, Jun (International Journal of Geosynthetics and Ground Engineering, 2019)
Granular materials such as soils, powders, and other particulate materials have been widely used in geotechnical engineering. In particular, sandy soils are one of the representative ones. Recently, there has been attention on environment-friendly materials such as tire chips or other waste materials. Besides, one of the key behaviors for these materials is shear behavior, including the effect of dilatancy. In this paper, direct shear behavior of sands as rigid particles and tire chips as elastic particles is discussed. Here, micro-focus-type X-ray-computed tomography (CT) scanner is used with direct shear tests to investigate the close behavior in granular materials. To discuss the results of CT scanning quantitatively, a digital image correlation method is used and then, the distribution of the displacements in the shear box, shear strain, and volumetric strain are measured using CT data. In addition, a series of numerical analysis using discrete element method (DEM), which is often used for granular materials, is carried out for the same cases as direct shear test to validate the CT results. Finally, based on the comparative discussion between test results with CT scanning and DEM results, the direct shear behavior of different granular materials is precisely investigated for the first time using X-ray CT. The use of tire chips mixed with sand decreases the dilatant behavior under shear stress, and the peaks in shear stress are no longer observed. In addition, tire chips seem to prevent shear bands to propagate in the material.